The Role of Islamic Education in Fostering Tolerance and Diversity in Indonesia’s Pluralistic Society - Mahmoud Abderaman Hassane; Aya Ragab; Erkinov Farrukh (Solo Universal Journal of Islamic Education and Multiculturalism, 2025)
Objective: This study examines the role of Islamic education in fostering tolerance and diversity in Indonesia’s pluralistic society. It focuses on how Islamic educational practices promote mutual respect, inclusivity, and peaceful coexistence across diverse cultural, ethnic, and religious backgrounds. Theoretical framework: The study is grounded in Islamic educational philosophy and Multicultural Education. Islamic education emphasizes moral values, social harmony, and the principle of rahmatan lil ‘alamin (mercy to all creation), while multicultural education promotes inclusivity, respect for diversity, and intercultural understanding. Literature review: Existing scholarship on Islamic education highlights its role in character formation, ethical development, and community cohesion. Meanwhile, studies on Multicultural Education emphasize the importance of inclusive curricula and pedagogies in fostering tolerance and addressing diversity in pluralistic societies. Method: This study employs a qualitative approach, with data collected through interviews, classroom observations, and document analysis in selected formal institutions such as schools and pesantren, as well as non-formal community-based learning environments. Results: The findings reveal that Islamic education significantly contributes to the development of tolerant attitudes when it integrates multicultural perspectives, emphasizes ethical teachings such as rahmatan lil ‘alamin, and adopts participatory and dialogical pedagogies. However, challenges persist, including rigid curricula, limited teacher training in multicultural education, and the presence of exclusive interpretations of religious texts. Implications: The study suggests that strengthening Islamic education through inclusive curricula, teacher capacity building, and contextualized learning approaches can enhance its role in nurturing unity in diversity. It underscores the need for educational reforms that align religious teachings with contemporary societal demands. Novelty: This study offers a contextual analysis of Islamic education in Indonesia by integrating Multicultural Education principles, highlighting its potential as a transformative tool for promoting tolerance and diversity in a pluralistic society.